Returns to public sector plant breeding in the presence of spill-ins and private goods: The case of bean research in Michigan - Maredia, Mywish K.; Bernsten, Richard; Ragasa, Catherine (Wiley, 2010)
This article illustrates a methodology for assessing economic returns to a publicly funded breeding program in the presence of private sector investments, and spill‐ins from other contemporary public institutions and past research efforts. The approach consists of determining yield gains from bean improvement research; applying these yield gain estimates to measure benefits attributable to different institutional players and time periods; and then assessing the benefit‐cost ratios of investments in a bean improvement program since 1980 by Michigan State University (MSU). The results indicate that investments in MSU's bean breeding program have yielded benefits to costs ratio in the range of 0.7 to 2.2, depending on the attribution rule used to estimate the benefits. The estimated benefit/cost ratios reported in this study are lower‐bound estimates, as they do not account for potential benefits from area planted to MSU varieties outside of Michigan (spillover effects), which was 1.5 times greater than the area planted to MSU‐bred varieties within Michigan in the period 1998–2002. The implications of the increasingly privatized bean seed markets for the role of public sector research in bean improvement research are discussed.